2015
DOI: 10.1161/strokeaha.115.008998
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter Integrity and Cognitive Functions in Patients With Subcortical Silent Lacunar Infarcts

Abstract: Background and Purpose-Silent lacunar infarct (SLI) is a risk factor for dementia. This study investigated the white matter integrity abnormality and its relationship to the cognition impairments in SLI patients. Methods-Between 27 patients with SLI in basal ganglia and 30 healthy controls, we assessed the difference in a batter of neuropsychological tests and in white matter integrity measurements, fractional anisotropy, and mean diffusivity, using tract-based spatial statistics. Results-Compared with healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
(16 reference statements)
3
29
0
1
Order By: Relevance
“…Patients with ESRD have lower FA and higher MD values[6, 1013], which are generally associated with poorer cognitive function[8, 9, 22, 23]. Moreover, improvement in FA and MD is associated with an improvement in cognition[24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ESRD have lower FA and higher MD values[6, 1013], which are generally associated with poorer cognitive function[8, 9, 22, 23]. Moreover, improvement in FA and MD is associated with an improvement in cognition[24].…”
Section: Discussionmentioning
confidence: 99%
“…Lower FA and higher MD values are associated with impaired cognition[8, 9]. Patients with ESRD have lower FA and higher MD values[6, 1013].…”
Section: Introductionmentioning
confidence: 99%
“…Fern et al demonstrated that tract-specific damage of WM and region-specific lesions and network disruption accompanied cognitive declines and eventually led to dementia. DTI of patients with lacunar infarcts reveal decreased FA and increased MD across several WM regions either close to or relatively far from lesions, implying that WM damage not only influences nearby areas, but also extends across considerable distances (Chen et al, 2015b). Lunven et al directed a prospective, longitudinal study that measured microstructural markers of neglect restoration after ischemia in the MCA territory (Lunven et al, 2015).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Until recently, this finding had been considered a benign accompaniment to aging. 1 However, accumulating evidences have shown that SBI is a clinically important precursor lesion of many adverse health outcomes, including cognitive decline 2 and clinical stroke. 3 SBI includes 2 subtypes, lacunar type (silent lacunar infarction [SLI]) and nonlacunar type.…”
mentioning
confidence: 99%